Prospective analysis of different combined regimens of stereotactic body radiation therapy and chemotherapy for locally advanced pancreatic cancer. (17th May 2018) - Zhu, Xiaofei; Shi, Dongchen; Li, Fuqi; Ju, Xiaoping; Cao, Yangsen; Shen, Yuxin; Cao, Fei; Qing, Shuiwang; Fang, Fang; Jia, Zhen; Zhang, Huojun
Abstract: To identify impacts of different combined regimens of stereotactic body radiation therapy (SBRT) and chemotherapy on survival of patients with locally advanced pancreatic cancer (LAPC) and factors correlated with determinations of different combinations. Four hundred and nineteen patients with radiographically and biopsy‐proven LAPC were prospectively enrolled. Factors associated with different strategies were analyzed with Chi‐square test and contingency coefficients. Cox regression was used to identify factors predictive of survival. Prognostic values of different multimodality were further analyzed by propensity score‐matched analysis. Median overall survival (OS) and progression‐free survival (PFS) of all patients was 13.2 and 8.2 months, respectively. Baseline ECOG correlated with induction chemotherapy, while tumor stage, lymph node invasion, and toxicity after SBRT associated with adjuvant chemotherapy. Patients with induction chemotherapy alone (12.2 months), adjuvant chemotherapy alone (13.6 months), and induction and adjuvant chemotherapy (13.3 months) had longer OS than those without chemotherapy (11.2 months; P < .001), while adjuvant chemotherapy alone and induction and adjuvant chemotherapy increased PFS. An adjusted overall survival benefit was gained with adjuvant chemotherapy compared with induction and adjuvant chemotherapy (OS: 14.7 months [95% CI: 14.2‐15.2 months] vs 13.1 months [95% CI: 12.3‐13.9 months]; P < .001) (PFS: 8.8 months [95% CI: 8.4‐9.2 months] vs 8.1 months [95% CI: 7.4‐8.8 months]; P = .053). Induction and adjuvant chemotherapy, especially adjuvant chemotherapy, plus SBRT may improve OS and PFS. Baseline performance status, tumor stage, lymph node involvement, and toxicity after SBRT influenced determinations of upfront multimodality. Abstract : No consensus has been reached on best combinations of upfront treatment modality for locally advanced pancreatic cancer. The pilot study showed that stereotactic body radiation therapy plus induction and adjuvant chemotherapy, especially adjuvant chemotherapy alone, may improve overall survival and progression‐free survival.